2019
DOI: 10.1371/journal.pone.0213184
|View full text |Cite
|
Sign up to set email alerts
|

Swainsonine, an alpha-mannosidase inhibitor, may worsen cervical cancer progression through the increase in myeloid derived suppressor cells population

Abstract: Cervical cancer, caused by high oncogenic risk Human Papillomavirus (HPV) infection, continues to be a public health problem, mainly in developing countries. Using peptide phage display as a tool to identify potential molecular targets in HPV associated tumors, we identified α-mannosidase, among other enriched sequences. This enzyme is expressed in both tumor and inflammatory compartment of the tumor microenvironment. Several studies in experimental models have shown that its inhibition by swainsonine (SW) led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
1
16
0
3
Order By: Relevance
“…Subsequent studies explored the in vivo effects of SW on melanoma, 29 Ehrlich ascites carcinoma, 30 colorectal cancer, 31 human liver cancer, 32 lymphoma, 33 and leukemia 34 ; the results showed that all patients obtained good therapeutic effects 30,32,34,35 . The specific mechanisms of action include the following effects (Figure 3): inhibition of α‐mannosidase II, 137,138 promotion of tumor cell apoptosis, 139 enhancement of the immune system, 140 increase of intracellular calcium ion concentration, inactivation of the PI3K/AKT/mTOR signaling pathway, and repression of miR‐92a 141 . As a novel anticancer drug candidate, the biosynthesis of SW has also received attention as recently reviewed 142 …”
Section: Bioactivities Of Indolizidine Alkaloidsmentioning
confidence: 99%
“…Subsequent studies explored the in vivo effects of SW on melanoma, 29 Ehrlich ascites carcinoma, 30 colorectal cancer, 31 human liver cancer, 32 lymphoma, 33 and leukemia 34 ; the results showed that all patients obtained good therapeutic effects 30,32,34,35 . The specific mechanisms of action include the following effects (Figure 3): inhibition of α‐mannosidase II, 137,138 promotion of tumor cell apoptosis, 139 enhancement of the immune system, 140 increase of intracellular calcium ion concentration, inactivation of the PI3K/AKT/mTOR signaling pathway, and repression of miR‐92a 141 . As a novel anticancer drug candidate, the biosynthesis of SW has also received attention as recently reviewed 142 …”
Section: Bioactivities Of Indolizidine Alkaloidsmentioning
confidence: 99%
“…Scientists found that CD68+ TAMs in cervical tumor presented a mixed CXCL10 (M1)/CD163+ (M2) pattern [35]. CD45+ and CD105+ are also unspecific for certain subtypes [81,87,88]. Increasing studies have focused on which subtype of macrophages the TAMs belongs to.…”
Section: Biomarkers Of Tamsmentioning
confidence: 99%
“…A atividade da α-manosidase no câncer pode ter seu efeito nas células tumorais, por meio da migração e invasão através de glicoproteínas, bem como por meio das células do microambiente tumoral. Utilizando-se um inibidor farmacológico da α-manosidase, observou-se aumento de células mielóides supressoras136 . Estas células demonstraram ser responsáveis pela supressão de resposta de células T anti-tumorais.…”
unclassified
“…A taxa de CST IV (e de certo modo CST III, com predominância de L. iners) não era diferente em mulheres HPV negativas ou HPV positivas/LSIL, mas substancialmente maior para mulheres com HSIL, sugerindo que a presença de microbioma depletado de diversidade de Lactobacillus pode estar mais Com a necessidade de desenvolver novas estratégias para detecção de lesões precursoras ou mesmo neoplásicas, estudou-se outra proteína, a α-manosidase.Utilizando o método de apresentação de fagos peptídeos (phage display), identificou-se sequências peptídicas com afinidade preferencial para linhagens celulares e tumores do colo do útero. Uma das sequências correspondeu à α-manosidase237 . Observou-se que os tecidos cervicais expressavam esta proteína, e que a expressão era maior em lesões de alto grau e câncer, em comparação com a mucosa normal.…”
unclassified
See 1 more Smart Citation